2022
DOI: 10.3389/fonc.2022.859938
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data of Different Immune Checkpoint Inhibitors for Non-Small Cell Lung Cancer in China

Abstract: BackgroundPatients treated with immunotherapy in the real-world may have significantly different responses to those meeting inclusion criteria for random controlled clinical studies. There is a partial overlap in approved indications for the use of the different immune checkpoint inhibitors (ICIs) currently available. A comprehensive assessment of the efficacy, safety and economic effects of various ICIs is a problem that clinicians need to address.MethodsAnalyzed real-world data was collected from non-small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…One study of realworld data on non-small cell lung cancer from China demonstrated that the efficacy of immunotherapies was poorer after second-or later-line treatment than after first-line treatment. 29 Taken together with these data and our results, the efficacy of atezolizumab plus bevacizumab may not be expected to be sufficient if atezolizumab plus bevacizumab is used after other systemic therapies. Nowadays, the majority of patients with advanced HCC selected atezolizumab plus bevacizumab as first-line systemic therapy in Japanese clinical practice based on the guidelines.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…One study of realworld data on non-small cell lung cancer from China demonstrated that the efficacy of immunotherapies was poorer after second-or later-line treatment than after first-line treatment. 29 Taken together with these data and our results, the efficacy of atezolizumab plus bevacizumab may not be expected to be sufficient if atezolizumab plus bevacizumab is used after other systemic therapies. Nowadays, the majority of patients with advanced HCC selected atezolizumab plus bevacizumab as first-line systemic therapy in Japanese clinical practice based on the guidelines.…”
Section: Discussionmentioning
confidence: 49%
“…The initial report with its short observation period, including 20 patients, showed differences in ORRs according to RECIST version 1.1 between the first‐line treatment group and second‐ or later‐line treatment group (26% vs. 0%). One study of real‐world data on non–small cell lung cancer from China demonstrated that the efficacy of immunotherapies was poorer after second‐ or later‐line treatment than after first‐line treatment 29 . Taken together with these data and our results, the efficacy of atezolizumab plus bevacizumab may not be expected to be sufficient if atezolizumab plus bevacizumab is used after other systemic therapies.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, the relatively small number of patients treated with induction chemoimmunotherapy and the subsequent analysis in the cCRT/sCRT setting further reduced the sample size, which, together with the relatively shorter follow-up period, may also affect the results. Finally, although this study did not distinguish the e cacy of different ICIs, a previous study reported no signi cant difference in the e cacy and safety among variable ICIs [23]. Nevertheless, future studies should focus on an identical ICI agent.…”
Section: Discussionmentioning
confidence: 57%
“…In this multicenter series on the use of ICIs from India, the responses and outcomes were comparable to those realworld data reported in literatures. [1][2][3][4] Financial constraints were the major factor limiting the use if ICIs. This was 4.6 months, and the median OS was 15.4 months.…”
Section: Discussionmentioning
confidence: 99%